EAHP European Statements baseline survey 2015: methodology. Issue 2 (24th February 2016) - Underhill, Jonathan; Gibbons, Nicholas
Abstract : The European Statements of Hospital Pharmacy are a set of hospital pharmacy practice standards published by the European Association of Hospital Pharmacists (EAHP) for European health systems to ensure safe, effective and optimal use of medicines in collaboration with multidisciplinary teams. Keele University was commissioned to conduct a survey among European hospital pharmacists to establish a baseline to assess awareness of the Statements and to identify any barriers to their implementation. The survey was conducted from January 2015 to March 2015, spanning 16 languages and 34 countries. The survey consisted of three sections: ▸ Section A: general questions about the participant's hospital pharmacy, such as workforce skill-mix and number of beds served; ▸ Section B: questions about the current activity of pharmacists around each statement; ▸ Section C: questions about the hospital's readiness and ability to implement the statements. In section B, a value was allocated to each response to rate the degree to which they were able to comply with each statement (where 1=never able to comply, 5=always complied). In section C, they were asked to what degree they agreed with the question (1 for strongly disagree, 5 for strongly agree). A response of 1 or 2 was deemed to indicate some difficulty in complying with that statement—a 'negative response'. Where this was the case, the participant was given the option to provide a free text response explaining the reasons for this difficulty. The full results are discussed in a subsequent paper (add link at publishing). Overall, the response rate was 18%, but the variation in this was marked. 22 of the 34 countries had a response rate of over 30%. The methods used for this survey results informs the methodology and scope of future EAHP surveys Recommendations for future surveys are as follows: ▸ Keep the survey short and easy to complete (to within 20 min); ▸ Specifically enquire for each question if capacity and capability are the key barriers to implementation; ▸ Construct survey response options for each question to identify barriers other than capacity and capability; ▸ Identify the key drivers for change in countries where implementation has occurred or is occurring; ▸ Compile better intelligence about the number of surveys sent out in the first place (as those countries with a low response rate sent out lots of invites to participate which may be unrealistic); ▸ A named person (country coordinator) to send out invite survey link; ▸ Weekly reminders should be sent out by the named person (country coordinator).